In vitro antioxidant and antimalarial activities of leaves, pods and bark extracts of Acacia nilotica (L.) Del. - Muhammad Bilal Sadiq; Pattamon Tharaphan; Kesinee Chotivanich; Joel Tarning; Anil Kumar Anal (BMC, 2017)
Abstract Background The emergence of drug resistant malaria is threatening our ability to treat and control malaria in the Southeast Asian region. There is an urgent need to develop novel and chemically diverse antimalarial drugs. This study aimed at evaluating the antimalarial and antioxidant potentials of Acacia nilotica plant extracts. Methods The antioxidant activities of leaves, pods and bark extracts were determined by standard antioxidant assays; reducing power capacity, % lipid peroxidation inhibition and ferric reducing antioxidant power assay. The antimalarial activities of plant extracts against Plasmodium falciparum parasites were determined by the 48 h schizont maturation inhibition assay. Further confirmation of schizonticide activity of extracts was made by extending the incubation period up to 96 h after removing the plant extract residues from parasites culture. Inhibition assays were analyzed by dose-response modelling. Results In all antioxidant assays, leaves of A. nilotica showed higher antioxidant activity than pods and bark. Antimalarial IC50 values of leaves, pods and bark extracts were 1.29, 4.16 and 4.28 μg/ml respectively, in the 48 h maturation assay. The IC50 values determined for leaves, pods and bark extracts were 3.72, 5.41 and 5.32 μg/ml respectively, after 96 h of incubation. All extracts inhibited the development of mature schizont, indicating schizonticide activity against P. falciparum. Conclusion A. nilotica extracts showed promising antimalarial and antioxidant effects. However, further investigation is needed to isolate and identify the active components responsible for the antimalarial and antioxidant effects.